Ancient Maya: The Rise and Fall of a Rainforest Civilization - Pineda, Anna C. L. (Hukay; Vol 9 (2006), 2016)
Book Review of Arthur Demarest's Ancient Maya: The Rise and Fall of a Rainforest Civilization.